Urgensi Pelatihan Long Tone terhadap Intonasi dalam Permainan Instrumen Saxophone pada Mahasiswa Pendidikan Musik di Universitas Negeri Padang - Benovan Rahmandicca; Robby Ferdian (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The purpose of this study was to evaluate the current intonation in Music Education students at UNP, assess the impact of longtone exercises in improving intonation, and assess intonation differences before and after training. This type of research is descriptive qualitative research research. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of interviews, observations, and document analysis. The steps of analyzing data are data reduction, data model and drawing conclusions. The results showed that longtone training became the most important exercise in the process of forming pitch control (intonation) in playing the Saxophone. Longtone exercises build the strength of the lip muscles (muscle memory) because to get a good intonation, the lip muscles must be formed and have stable strength in order to get a good tone, because the Saxophone is a tool that is very sensitive to pitch changes. Researchers provide an understanding of the urgency and mastery of basic exercises in playing beginner Saxophone. Because before mastering higher techniques, of course, you must master basic techniques first, especially longtones, so that higher technique training does not experience problems because it already has a strong foundation. This research also provides an understanding that it is important for an instrument player to perform the stages in the process of musical instrument practice well and the importance of practicing basic techniques in learning the instrument.